The impact of inflationary recession in developed countries on the developing world : U.N. conference on trade and development - United nation (Geneva : United State, 1978)
This book examines the effects of inflation in developing countries including the structural imbalances that emanated as a factors in generating world inflation and recession.
asm; 06/03/19
Loans
Keywords: Economy history; Developing countries